Multiple Rounds of Artificial Selection Promote Microbe Secondary Domestication—The Case of Cachaça Yeasts. (2nd July 2018) - Barbosa, Raquel; Pontes, Ana; Santos, Renata O; Montandon, Gabriela G; de Ponzzes-Gomes, Camila M; Morais, Paula B; Gonçalves, Paula; Rosa, Carlos A; Sampaio, José Paulo
Abstract: The study of microbe domestication has witnessed major advances that contribute to a better understanding of the emergence of artificially selected phenotypes and set the foundations of their rational improvement for biotechnology. Several features make Saccharomyces cerevisiae an ideal model for such a study, notably the availability of a catalogue of signatures of artificial selection and the extensive knowledge available on its biological processes. Here, we investigate with population and comparative genomics a set of strains used for cachaça fermentation, a Brazilian beverage based on the fermentation of sugar cane juice. We ask if the selective pressures posed by this fermentation have given rise to a domesticated lineage distinct from the ones already known, like wine, beer, bread, and sake yeasts. Our results show that cachaça yeasts derive from wine yeasts that have undergone an additional round of domestication, which we define as secondary domestication. As a consequence, cachaça strains combine features of wine yeasts, such as the presence of genes relevant for wine fermentation and advantageous gene inactivations, with features of beer yeasts like resistance to the effects of inhibitory compounds present in molasses. For other markers like those related to sulfite resistance and biotin metabolism our analyses revealed distributions more complex than previously reported that support the secondary domestication hypothesis. We propose a multilayered microbe domestication model encompassing not only transitions from wild to primarily domesticated populations, as in the case of wine yeasts, but also secondary domestications like those of cachaça yeasts.